Subglacial water drainage, storage, and piracy beneath the Greenland ice sheet. Issue 18 (30th September 2015) - Lindbäck, K.; Pettersson, R.; Hubbard, A. L.; Doyle, S. H.; van As, D.; Mikkelsen, A. B.; Fitzpatrick, A. A.
Abstract Meltwater drainage across the surface of the Greenland ice sheet (GrIS) is well constrained by measurements and modeling, yet despite its critical role, knowledge of its transit through the subglacial environment remains limited. Here we present a subglacial hydrological analysis of a land‐terminating sector of the GrIS at unprecedented resolution that predicts the routing of surface‐derived meltwater once it has entered the basal drainage system. Our analysis indicates the probable existence of small subglacial lakes that remain undetectable by methods using surface elevation change or radar techniques. Furthermore, the analysis suggests transient behavior with rapid switching of subglacial drainage between competing catchments driven by seasonal changes in the basal water pressure. Our findings provide a cautionary note that should be considered in studies that attempt to relate and infer future response from surface temperature, melt, and runoff from point measurements and/or modeling with measurements of proglacial discharge and ice dynamics.